The Impact of Electromagnetic Gadgets on the Physical Health of Children Under 14 Years Old in the City of Bandung - Efka Fatikha, Amanda Syahira; Firmansyah, Doni; Hamdani, Neng Widia; Euniqe, Revalina (Jurnal Medisci, 2024)
The development of information technology has penetrated all ages. The use of gadgets is inseparable in daily life. Gadgets have a greater negative impact on children under the age of 14 years. This study aims to determine the impact of electromagnetic gadgets on children's physical health. The research was conducted in the city of Bandung. The methods used in this study are descriptive methods and literature studies. The questionnaire sheet was distributed to 20 resource persons: Housewives, Employees, Civil Servants, Researchers, Traders and Entrepreneurs. The results of the study show that the existence of gadgets can affect the physical health of children under 14 years old in the city of Bandung. The influences are positive and negative. The factors that can trigger these various impacts can be known to come from the facilities and the level of supervision of parents who have children under 14 years old. Apart from the negative impact that can trigger poor physical health in children under 14 years old in Bandung itself, respondents stated that it is very important to have gadgets to make it easier for parents and children to carry out their daily activities.